Legitimacy-Seeking Organizational Strategies in Controversial Industries: A Case Study Analysis and a Bidimensional Model - Reast, Jon (Journal of business ethics, 2013)
Controversial industry sectors, such as alcohol, gambling, and tobacco, though long-established, suffer organizational legitimacy problems. The authors consider various strategies used to seek organizational legitimacy in the U.K. casino gambling market. The findings are based on a detailed, multistakeholder case study pertaining to a failed bid for a regional supercasino. They suggest four generic strategies for seeking organizational legitimacy in this highly complex context: construing, earning, bargaining, and capturing, as well as pathways that combine these strategies. The case analysis and proposed bidimensional model of generic legitimacy-seeking strategies contribute to limited literature on organizational legitimacy in controversial industry sectors. In addition, beyond organizations active in controversial contexts, this study and its implications are useful for individuals and organizations supporting or opposing the organizational legitimacy of organizations in controversial industries.